Faculty of Pharmacy annual dean's speech & Hari Raya Aidilfitri gathering / Azlinda Mohd Nor and Dr. Gurmeet Kaur Surindar Singh - Mohd Nor, Azlinda; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On May 10th, 2023, the administration of the Faculty of Pharmacy, Universiti Teknologi MARA organised a 'Dean's Annual Speech and Interactive Session' for staff members with the goal of disseminating important information, updates, insights, and upcoming plans within the faculty. The interactive session, attended by faculty members, aimed to foster collaboration, improve communication, and ensure that staff members are well-informed about significant developments within the faculty. Such gatherings are held periodically to foster collaboration, promote effective communication, and ensure that staff members are well-informed about significant developments and new directions within the faculty and university.